A COMPARATIVE STUDY OF THE OUTCOME OF TYMPANOPLASTY USING METHYLENE BLUE STAINED AND UNSTAINED TEMPORALIS FASCIA GRAFT: A COHORT STUDY - Kumar, Ramesh; Shankar, Daya; Saxena, Shikhar; Singh, Hitendra Prakash (Student's Journal of Health Research Africa, 2025)
Background An inflammatory condition that affects both the middle ear space and the mastoid air cell system, chronic suppurative otitis media causes long-term or irreversible alterations in the tympanic membrane, such as atelectasis, dimeric or monomeric formation, perforation, tympanosclerosis, the formation of a retraction pocket, or cholesteatoma. Objectives The study's objective was to assess and contrast the results of tympanoplasty utilizing unstained temporalis fascia graft and methylene blue stain, as well as the functional outcomes of patients based on follow-up. Materials and Methods It was a comparative prospective cohort research conducted at a single center. The study was carried out between 2020 and 2021, or for a total of one year. Ear, nose, and throat (ENT) research was conducted at King George's Medical University (K.G.M.U.) in Lucknow, Uttar Pradesh, India. Eighty patients in all took part in the study. Results The study compared tympanoplasty outcomes using unstained versus methylene blue-stained temporalis fascia grafts. Both groups showed significant improvements in air conduction and air-bone gap (p<0.001). Post-operative complaints and graft integrity were similar between the groups. Graft integrity remained intact in 87.5% (Group I) and 82.5% (Group II) cases at 3 months. Conclusion According to the study's findings, between the groups' pre-operative symptoms and otoscopic findings, there was no meaningful difference. Mean changes in air conduction thresholds and air-bone gap values were significantly different among the study groups. Recommendation It is recommended to consider both unstained and methylene blue-stained temporalis fascia grafts as effective options for tympanoplasty, with similar functional outcomes and graft integrity.